Time to Disease Control with Dupilumab for Bullous Pemphigoid: A Systematic Review and Meta-analysis - Laurence Mainville; Lily Xu; Vincent Piguet; Aaron M. Drucker; David O. Croitoru (Acta Dermato-Venereologica)
Bullous pemphigoid (BP) is a chronic autoimmune blistering disease primarily affecting the elderly population. While awaiting the results from randomized clinical trials to assess the effect of dupilumab in patients with BP, clinicians have begun to introduce dupilumab into their therapeutic arsenal, with few data supporting their clinical decisions. The objectives were to assess time to disease control, predictors of response, achievement of disease control, disease recurrence, and occurrence of adverse events. Randomized and non-randomized studies of interventions (NRSIs) from Medline and Embase were reviewed. A total of 315 studies were identified and 5 NRSIs (167 participants with moderate-to-severe BP) meeting our inclusion criteria were found. Dupilumab was significantly associated with shorter time to disease control compared with the control group (HR 2.71  [95% CI, 1.85–3.96; I2 = 35%; 127 participants; 4 studies]). The overall strength of the evidence was graded as very low due to serious risk of bias and imprecision of effect measures. There were insufficient data to inform conclusions regarding BP recurrence and adverse events. Evidence was found that dupilumab reduces time to disease control in BP. It was not possible to assess predictors of response using pre-planned meta-regression. Randomized controlled trials are needed to determine dupilumab’s place in therapeutic algorithms for BP.